Algebra

Solve by using the quadratic formula.
3x^2=11x+4.

Look up the formula if you don't know it already.

In this case a = 3, b = -11 and c = -4.

You get that by rewriting the equation in the standard form ax^2 + bx + c = 0 , where a, b, and c are constants.

  1. 👍 0
  2. 👎 0
  3. 👁 66
asked by Shaye

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math

    Use the quadratic formula to solve each of the following quadratic equations... 1. 2x^2-5x=3 2. 3x^2-2x+1=0 Rearrange the equation in quadratic formula form. 2x^2 -5x -3 = 0 Then use the formula. Tell me what you don't understand

    asked by Tomika on June 13, 2007
  2. math,algebra

    can someone help me out factor out this 0=16t^2-122t+180 i have so far this but the last one i am not sure 8(2t^2-14t + ?) you need to use the quadratic formula: -b(+or-)[sqrt(b^2-4ac)/2a] so you are saying that i don't have to

    asked by jasmin20 on April 6, 2007
  3. Math

    Solve for the zeros of the function using the quadratic formula. 3x^2=-4x+6 I know what the quadratic formula is but when I put it into the formula I keep getting an error on the graphing calculator.

    asked by M on April 9, 2015
  4. Algebra

    I was given this answers to a problems I solved but I do not understand what she means hope you can help. Before attempting to solve this quadratic equation, determine how many solutions there will be for this quadratic equation.

    asked by Charly on June 2, 2011
  5. Algebra

    I was given this answers to a problems I solved but I do not understand what she means hope you can help. Before attempting to solve this quadratic equation, determine how many solutions there will be for this quadratic equation.

    asked by Charly on June 2, 2011
  6. math

    (4.35E-2 - x)(7.56E-2 -x ) ============================ (0.324 + 2x)2 Rearrange to get an expression of the form ax2 + bx + c = 0 and use the quadratic formula (solve for x. This gives: x = 1.05E-2, 0.143 basically i understand

    asked by bob on March 10, 2012
  7. Help With Math

    Using the quadratic formula to solve equations. -12^2 + 12 x-9 = -7x^2 10x^2 + 5x + 12 = 0 6x^2 + 12x = - 1 11x^2 - 7x -1 = 0 2x^2 -18x + 16 = 0 Can u show work to help me out

    asked by Monte' on November 13, 2007
  8. algebra

    how would i work out the following problems solve each formula in terms of the given variable 1. 5d-2g=9 ;g The formula A=2h(l+w) gives the lateral area a of a rectangular solids with length l, width,w and height h. 2. solve this

    asked by jessica on September 22, 2008
  9. College Math II

    Solve by using the quadratic formula. x^2 + 6x + 6 = 0 I am having problems using the quadratic formula to get the right answer. Can someone show me the steps that I use? Thanks.

    asked by Lori on November 21, 2009
  10. Algebra

    Use the quadratic formula to solve the equation. Give exact answers. 2x^2 + 11x - 21 = 0 a) -3/2, 7 b) 3/2, -7 c) 3/2, 7 d) -3/2, -7 I could not get any of these answers.

    asked by Cassie on June 6, 2009

More Similar Questions